Should We Revisit the Clinical Value of Fractional Flow Reserve in the Era of Coronary Microvascular Dysfunction? - Georgiana Pintea Bentea; Ahmad Awada; Brahim Berdaoui (Biomedicines)
The understanding of coronary artery disease is evolving, with more attention given currently to the microcirculation compartment. Coronary microvascular dysfunction (CMD) is defined by any structural or functional alteration of the coronary microcirculation, and is prevalent in current clinical practice, being associated with pejorative cardiovascular prognosis. CMD can exist by itself as primary microvascular angina, or in association with a variety of cardiovascular diseases. On the other hand, fractional flow reserve (FFR) represents the gold standard for estimating the hemodynamic impact of moderate coronary artery stenosis, and as such guiding coronary revascularization in clinical practice. The fundamental clinical trials that introduced and validated the use of FFR in current clinical practice were published before acquiring more in-depth knowledge on CMD and the impact it can have on FFR measurements. However, in the setting of CMD, studies have shown that FFR can underestimate the severity of coronary stenosis. In addition, recent findings underline the limitations of FFR to guide revascularization in terms of clinical outcome in specific conditions associated with CMD, such as acute coronary syndrome or multivessel coronary artery disease. As such, new research efforts must be made to investigate the reliability of FFR or to reposition its use in guiding coronary revascularization in the context of CMD, in order to define the clinical value of FFR in this particular setting.